The Effectiveness of the controversial experimental approach in chemistry achievement and the nature of scientific knowledge for fifth scientific grade students - Maher Jalil, Wasan (Opción, 2019)
The aim of the research is to know the effectiveness of the experimental dialec- tical approach in the level of academic achievement in the subject of chemistry and the nature of scientific knowledge of fifth-grade students in a scientific manner. In order to achieve these goals, the researcher applied the experimen- tal approach with the two equal independent groups. The number of its mem- bers reached (70) students, who were divided into two groups, one of which was a number of (35) studied in the usual way, and a pilot group of (35) studied using the experimental dialectical approach, parity was carried out between the two groups of research in the variables) Keep in chemistry, the nature of scientific knowledge), and to apply the research experience, the research tools are designed and are the achievement test, and a questionnaire (scale) the na- ture of scientific knowledge (prepared by the researcher) and after verification of the stability and validity of the tools and their arbitration by experts and arbitrators specialized in chemistry science and methods Teaching chemis- try, the experiment was applied in the second semester of the academic year 2018-2019, as the two experimental research groups were taught according to the experimental dialectical approach and the control group according to the usual method. One of the research tools was applied before and after, and to test the validity of the assumptions, data was collected, and then statistically analyzed using the appropriate statistical means, and the research reached several results, most notably: 1- The effectiveness of the experimental dialec- tical approach in raising the level of achievement of the chemistry subject for fifth-grade students. 2- The effectiveness of the experimental dialectical approach in develop- ing and improving the students ’understanding of the nature of scientific knowledge, and in light of the research results, the researcher recommend- ed several recommendations, including: Applying the experimental dialec- tical approach to teaching chemistry because of its clear impact on acquir- ing chemical concepts and developing the skills of laboratory experiments associated with it.